Clinical features and therapeutic outcome of 30 patients diagnosed with primary myelofibrosis at the national center of hematology - Alwan, Alaa F. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Primary myelofibrosis is characterized by clonal expansion of hematopoietic stem cell with a non-reactive clonal proliferation of fibroblasts and bone marrow fibrosis, which occurs at an extramedullary hematopoiesis. The clinical features of Primary myelofibrosis include anemia, marked splenomegaly and constitutional symptoms. Ineffective erythropoiesis and extra-medullary hematopoiesis are the main causes of anemia and organomegaly, respectively Objectives : the aim of this study was to evaluate the clinical features, diagnostic tools and the treatment outcome of patients with primary myelofibrosis.Patients and methods: this is a prospective study conducted at the national center of hematology in Baghdad during the period between October 2009 and October 2013. It includes 30 adult patients diagnosed with primary myelofibrosis. Diagnosis was based primarily on bone marrow aspirate and biopsy. The patients were followed up and assessed monthly with complete blood picture and liver function test and renal function test with serum lactate dehydrogenase level.Results: thirty patients were included in this study. There were 16 male and 14 female, the median age was 58 year with range (26-75) years. The most frequent presentation was in the group older than 60 years. Twenty four (80 %) patients had symptoms at diagnosis. The most frequent presentation were the fatigue, left upper quadrant swelling, night sweats, weight loss and fever. The main clinical features were huge splenomegaly which is found in 29 (97%) of patients, while the main finding in blood count at presentation were anemia followed by leukocytosis with leukoerythroblastic blood picture in 22 (73 %) of cases. The level of LDH was high in about 23 (77 %). The bone marrow biopsy showed fibrosis stage 2 in 24 (80 %).Patients who died were in the highest risk groups. The median survival was approximately 28 months.Conclusion: Primary myelofibrosis is part of myeloproliferative neoplasia; it usually runs chronic course. Till now none of the therapeutic modalities approved for treatment of primary myelofibrosis proved to be superior to others, yet the 5 year survival of this disease considered good.